Strategi Kesiapan Koperasi dalam Digitalisasi Perkebunan Kelapa Sawit Rakyat - A Faroby Falatehan; Yusman Syaukat; Hariyadi Hariyadi; Sriwulan Ferindian Falatehan (Institut Pertanian Bogor, 2021)
KUD Tunas Muda is one of the cooperatives active in using information technology to serve the needs of its members, especially related to oil palm activities. However, not all palm oil activities have been carried out through digitization. This paper aims to provide an overview of the readiness of the KUD located in Riau Province in digitizing smallholder oil palm plantations, which include activities in preparing inputs, cultivation, marketing, and receiving payments. This study also aims to analyze strategic priorities that cooperatives can carry out in digitizing smallholder palm oil. This study uses two methods in its analysis, namely descriptive analysis, and analytical hierarchy process. Based on the study, cooperative management is quite prominent in initiating and building digital systems in services for their members. This is because the KUD already has experience in digitalization, although the function is still limited. According to the analysis, the prioritized strategy is to increase the understanding of oil palm farmers, especially among members, in using digital technology and information to support the digitalization of oil palm plantations. Keywords: analytical hierarchy process, cultivation, information technology, KUD Tunas Muda, smallholder plantation